Serial multiple mediation of psychological capital and self-directed learning ability in the relationship between perceived stress and professional identity among undergraduate nursing students in China: a cross-sectional questionnaire survey - Xiu-Juan Feng; Xiao-Hui Chai; Huan Liu; Xiang-Xiang Li; Chun-Ni Heng; Jing-Hui Tong; Wen-Kai Zheng (BMC Medical Education)
Abstract Background Professional identity has a positive impact on the career development, job satisfaction, and job performance of undergraduate nursing students, and it is also an important foundation for their future nursing careers. Therefore, it is necessary to explore the influencing factors of professional identity and the inherent relationships between these factors. Objective This study aims to investigate the serial multiple mediating effect of psychological capital and self-directed learning ability in the relationship between perceived stress and professional identity among undergraduate nursing students. Methods All participants (n = 596) were collected using an online survey between October 2023 to January 2024 through cluster sampling. Measures of perceived stress, psychological capital, self-directed learning ability, and professional identity were assessed. The serial multiple mediation of psychological capital and self-directed learning ability in the relationship between perceived stress and professional identity was examined using the SPSS PROCESS 3.4 macro by Hayes. Data analysis included descriptive analysis, independent samples t-tests, one-way ANOVA, Pearson's correlation, ordinary least-squares regression, and the bootstrap method. Results Professional identity was negatively correlated with perceived stress (r = -0.414, p < 0.001), and was positively correlated with psychological capital (r = 0.495, p < 0.001) and self-directed learning ability (r = 0.443, p < 0.001). In the model of perceived stress → psychological capital → self-directed learning ability → professional identity, the overall mediated effect was -0.567 (95% CI: -0.707 ~ -0.443), and the mediating effect of psychological capital was -0.365 (95% CI: -0.501 ~ -0.237), accounting for 46.09% of total effect. The mediating effect of self-directed learning ability was -0.083 (95% CI: -0.150 ~ -0.028), accounting for 10.48% of total effect. The serial mediating effect of psychological capital and self-directed learning ability was -0.120 (95% CI: -0.184 ~ -0.065), accounting for 15.15% of total effect. Conclusions Psychological capital and self-directed learning ability serve as chain mediators between perceived stress and professional identity among undergraduate nursing students. This indicates that nursing educators can enhance the psychological capital and self-directed learning ability of nursing students to reduce the adverse effects of perceived stress on their professional identity.